Trauma abdominal y sus complicaciones en pacientes adultos. - Cynthia Vanessa, Díaz Barahona (2020)
Introduction: Trauma is defined as a severe injury at the organic level, resulting from acute exposure to energy in amounts that exceed physiological tolerance. The abdomen is one of the most affected anatomical regions in traumatic injuries, estimated to be involved in 31% of polytrauma patients. In abdominal trauma, there are factors that condition the appearance of complications, whether early or late. The management for patients with these injuries is based mainly on the application of triage and timely diagnostic methods. Objective: To determine the main complications of abdominal trauma that occur in adult patients through the analysis of scientific articles. Methodology: A systematic search was conducted in regional and globally indexed journals such as Pubmed, Scielo, Journal of the American Medical Association (JAMA), American Journal of Emergency Medicine, World Journal of Surgery. Results: Out of a total of 67 bibliographies reviewed in which meta-analyses, systemic reviews, studies, clinical trials, clinical guidelines, and other references with scientific evidence were included. It was established that closed abdominal trauma has a higher prevalence rate than open abdominal trauma. The most used scale in triage for trauma patients is the Glasgow scale. The most used diagnostic method in health centers is the FAST because of its high specificity. The most common complications are late complications such as surgical wound infection, and the main early complication is a hemorrhagic shock.